The Effect of Alcohol Consumption on Periodontal Disease - Tezal, Miné; Grossi, Sara G.; Ho, Alex W.; Genco, Robert J. (Journal of periodontology (1970), 2001)
Background: Alcohol consumption, like smoking, may be related to periodontal disease independently of oral hygiene status. This study assessed the relationship between alcohol consumption and severity of periodontal disease. Methods: A cross‐sectional study of 1,371 subjects ages 25 to 74 in the Erie County, NY population was performed. Alcohol intake was assessed by means of previously validated selfreported questionnaires. Outcome variables were gingival bleeding, clinical attachment loss, alveolar bone loss, and presence of subgingival microorganisms. Results: Logistic regression analyses adjusting for age, gender, race, education, income, smoking, diabetes mellitus, dental plaque, and presence of any of 8 subgingival microorganisms showed that those consuming ≥5 drinks/week had an odds ratio (OR) of 1.65 (95% CI: 1.22 to 2.23) of having higher gingival bleeding, and OR of 1.36 (95% CI: 1.02 to 1.80) of having more severe clinical attachment loss compared to those consuming <5 drinks/week. Those consuming ≥10 drinks/week had an odds ratio (OR) of 1.62 (95% CI: 1.12 to 2.33) of having higher gingival bleeding and OR of 1.44 (95% CI: 1.04 to 2.00) of having more severe clinical attachment loss compared to those consuming <10 drinks/week. Alcohol consumption was not significantly related to alveolar bone loss nor to any of the subgingival microorganisms. Conclusions: The results suggest that alcohol consumption is associated with moderately increased severity of periodontal disease. Longitudinal studies are needed to determine whether alcohol is a true risk factor for periodontal disease. J Periodontol 2001;72:183‐189.